Diverse Roles of TgMIC1/4/6 in the Toxoplasma Infection - Zhu, Jinjin; Wang, Yang; Cao, Yuanyuan; Shen, Jilong; Yu, Li (Frontiers in Microbiology, 2021)
Toxoplasma gondii microneme (MIC) is a specialized secretory organelle that discharges its contents at the apical tip of this apicomplexan parasite in a sequential and regulated manner. Increasing number of studies on microneme proteins（MICs） have shown them as a predominant and important role in host cell attachment, invasion, motility and pathogenesis. In this review, we summarize the research advances in one of the most important MICs complexes, TgMIC1/4/6, which will contribute to improve the understanding of the molecular mechanism of T. gondii infection and provide a theoretical basis for the effective control against T. gondii.